Influence of intense soft X-ray radiation on the parameters of tracks induced in CR-39 and PM-355 solid state nuclear track detectors. (December 2015) - Szydłowski, A.; Malinowska, A.; Szewczak, K.; Jaskóła, M.; Korman, A.; Paduch, M.; Kuk, M.
Abstract: This paper presents the results of the influence of soft X-ray radiation on craters induced in SSNTDs by energetic α particles and protons of energy in the MeV range. We checked two detectors of the PM-355 and CR-39 types in order to verify and compare their resistance to the harsh conditions of high-temperature plasma experiments. To determine this effect some detector samples were first irradiated with α particles emitted from natural α particle sources and protons delivered by a particle accelerator. After that these samples were exposed to soft X ray radiation emitted from an X ray tube and also from the PF-1000 Plasma Focus facility. Doses during X ray irradiations varied from 0 up to tens of kGy. The irradiated samples were then etched in steps and track diameters were determined versus the absorbed dose and etching time and compared with those measured in samples not exposed to X ray radiation. Highlights: We present the results of the influence of soft X ray radiation on craters induced in SSNTDs. We checked two detectors of the PM-355 and CR-39 types. The CR-39 detector is more resistant to X ray radiation than the PM-355 one. The results demonstrate that the soft X ray can have considerable influence on nuclear track detectors.